Characterisation of Vaccinium Sect.Cyanococcus Mediated Synthesis of Hafnium Oxide Snanoparticles and its Cytotoxic Effect against Fibroblast Cell Line - Dr. Surabhi; Dr. Rajesh Kumar.S (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction Green synthesized Hafnium oxide nanoparticles (HfONPs) can be prepared for various other applications to address oral health concerns like bacterial infections and inflammation. Hafnium oxide nanoparticles exert their antimicrobial, anti-inflammatory and antioxidant effects through mechanisms like producing reactive oxygen species and direct interaction with microbial cells. Aim The present research article describes the anti-microbial, anti-inflammatory and antioxidant activity of green synthesised of Hafnium oxide nanoparticles (HfONPs) using Vaccinium sect.cyanococcus extract. Materials and Methods The Vaccinium sect. Cyanococcus mediated Hafnium oxide nanoparticles were developed and tested for various applications.These Hafnium oxide nanoparticles were characterized using UV-visible spectroscopy and Scanning electron microscopy.The antimicrobial activity of HfONPs was assessed using Mueller hinton agar plates. The anti-oxidant was evaluated using 2,2-diphenyl-1-picryl hydrazyl (DPPH), hydrogen peroxide (H2O2) assay methods. The anti-inflammatory activity was determined through the egg albumin denaturation method, the bovine serum albumin denaturation method, and the membrane stabilization assay. Results The present study gave insight about the anti-inflammatory, antioxidant and antimicrobial activity. There was a positive outcome when testing for Antimicrobial activity showing maximum zone of inhibition in C.albicans. Conclusion The green synthesised hafnium oxide nanoparticles using Vaccinium sect.cyanococcus showed an excellent antimicrobial, anti-inflammatory and antioxidant activity suggesting its potential for oral application and other inflammatory conditions.